The Effect of the Use of Animated Video Media on the Learning Outcomes of Pancasila Education for the Rights and Obligations of Grade IVB Students at SD Negeri 094155 Rambung Merah - Sri Jessica Matondang; Eva Pasaribu; Sukardo Sitohang (International Journal of Technology and Education Research, 2026)
The purpose of this study was to determine the effect of animated video media on the learning outcomes of Pancasila Education of class IVB students of SD Negeri 094155 Rambung Merah. This study is a quantitative study using a pre-experimental design in the form of One Group Pretest-Posttest Design. The sample in this study amounted to 30 students. The data collection technique used a test in the form of multiple choice questions. Before being given treatment, a pretest was conducted with an average value of 62.50. After being given treatment using animated video media, a posttest value was obtained with an average of 88.40. This shows that the posttest value is higher than the pretest value so that there is an increase in student learning outcomes. The results of the normality test using the Shapiro-Wilk test show that the pretest and posttest data are normally distributed because the significance value is greater than 0.05. Based on the results of the N-Gain test, an average value of 0.72 is obtained which is included in the high category. Furthermore, the results of the hypothesis test (t-test) obtained a t-count value of 18.345 with a significance level of 0.000. Since the significance value is less than 0.05 and t count > t table (18.345 > 1.699), H0 is rejected and Ha is accepted. Thus, it can be concluded that there is an effect of animated video media on the learning outcomes of Pancasila Education for class IVB students of SD Negeri 094155 Rambung Merah in the 2025/2026 academic year.